A study on the interaction of motorcyclists and other road users on roadways - Wan Ahmad, Wan Mariati Rohaya (1995)
Although much-effort has been devoted to the study of road accidents in Malaysia, it is only until recently little attention had been given to the accidents involving motorcyclists. Motorcyclists and pillion passengers who are involved in an accident may suffer a serious risk of sustaining severe injury. This study, therefore was designed particularly to determine the interaction between motorcyclists and other road users as well as to observe the behaviour of motorcyclists while riding. Spot speed data, traffic volume and types of faults made by motorcyclists were gathered simultaneously during three different traffic conditions at three locations which have been selected as the case study. The motorcyclists observed were chosen at random and were probably not aware that they were being watched. The results form the study indicates that traffic condition and roadways, in general, did not influence the behaviour of the motorcyclists. In general, at least 83-97 percent of the motorcyclists are accident prone due to careless riding. The most common faults made, at all locations, were associated with headlights 'off, safety gap, positioning and lane swap. In terms of speed selection, there are as high as 50 per cent of motorcyclists fail to ride at safe speed limit imposed on a particular road especially during off-peak hour. Immediate safety measures need to be taken to rectify this situation. Motorcycle lane should be provided along the roadways where large number of motorcycles passing through. Motorcyclists should also make themselves 'visible' and learn proper riding techniques before operating the machines.